2005
DOI: 10.1158/1055-9965.epi-05-0493
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Endometrial Cancer: A Hypothesis

Abstract: Endometrial cancer is the most common gynecologic malignancy in the United States. Substantial epidemiologic data implicate an imbalance of estrogens and progestogens in the etiology of this disease. We propose that inflammation also plays a role in endometrial cancer development. Emerging laboratory data suggest that elevated levels of prostaglandin E 2 may underlie the transformation of normal endometrium to neoplastic tissue and that in vitro nonsteroidal anti-inflammatory drugs may inhibit endometrial canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
212
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(215 citation statements)
references
References 139 publications
1
212
1
1
Order By: Relevance
“…Production of this cytokine, in both the KLE and RL95 endometrial adenocarcinoma cell lines after oestrogen stimulation, has also been demonstrated (He et al 2009). Other inflammatory mediators upregulated by oestrogen include IL1, TNF-a, and matrix metalloproteinases (MMPs) (Modugno et al 2005, He et al 2009, and IL1B can enhance the actions of oestrogen (King et al 2009). Oestrogen can also activate nuclear factor kappa-light-chain-enhancer of activated B cells (NFkB) signalling in endometrial cancer, a key transcription factor regulating the expression of many inflammatory mediators (Seo et al 2004).…”
Section: Oestrogen Progesterone and Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…Production of this cytokine, in both the KLE and RL95 endometrial adenocarcinoma cell lines after oestrogen stimulation, has also been demonstrated (He et al 2009). Other inflammatory mediators upregulated by oestrogen include IL1, TNF-a, and matrix metalloproteinases (MMPs) (Modugno et al 2005, He et al 2009, and IL1B can enhance the actions of oestrogen (King et al 2009). Oestrogen can also activate nuclear factor kappa-light-chain-enhancer of activated B cells (NFkB) signalling in endometrial cancer, a key transcription factor regulating the expression of many inflammatory mediators (Seo et al 2004).…”
Section: Oestrogen Progesterone and Inflammationmentioning
confidence: 99%
“…Progesterone also stimulates the production of prostaglandin dehydrogenase and inhibits cytokine-induced transcription of cyclooxygenase2 (COX2), thereby reducing prostaglandin production and consequent inflammation (Ishihara et al 1995, van der Burg & van der Saag 1996 Therefore, as endometrial adenocarcinoma is characterised by increased oestrogen to progesterone signalling, an increase in inflammatory mediators may occur, thus promoting tumour growth. The pro-inflammatory milieu in endometrial cancer can also directly increase oestrogen production (Modugno et al 2005). IL6 can stimulate oestrogen synthesis and can act synergistically with TNF-a to increase aromatase, 17b-hydroxysteroid dehydrogenase and oestrone sulfatase activity, thus increasing local oestrogen biosynthesis (Modugno et al 2005, Salama et al 2009).…”
Section: Oestrogen Progesterone and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…The transforming tissues exude prostaglandins and cyclooxygenases. Irreversible malignant proliferation of the endometrium takes place (413,414).…”
Section: Ebvmentioning
confidence: 99%
“…These white blood cells are often associated with the combating of infection and are also associated with inflammation. Inflammation may be associated with endometrial cancer and cell transformation [30]. An infiltration of eosinophil leukocytes has been reported in the uterus of rats after exposure to M. spicata, which causes lipid peroxidation and uterine damage [31].…”
Section: Changes In Uterine Morphologymentioning
confidence: 99%